Essays on Financial Analytics Applications and Methods - Alphonse, Pascal; Bouaiss, Karima; Grandin, Pascal; Zopounidis, Constantin (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book covers recent research advances, methods and techniques, applications and projects in financial analytics, with a focus on the effects of the health crisis on banking activities and financial engineering. It explores the latest developments in banking regulation, banking and financial systems, financial engineering, and corporate finance in order to provide financial analytics that assess financial stability and sustainability. Written for researchers and practitioners alike, the book is intended to promote stimulating scientific exchanges, ideas and experiences in the field of financial analytics for economics and management.
Foreign exchange risk hedging policy: Evidence from France -- Use of Financial Instruments among the Chilean households -- IFRS 9 -Financial Assets: Debt Instrument Classification and Management under the new Accounting Standard. A case study of Greek Government Bonds, in Banks' Investment Portfolios.-Investor Attention and Bitcoin Trading Behaviors -- An answer to Roll's critique (1977) forty five years later -- Detecting Equity Style Information within Institutional Media -- An Advanced Approach to Algorithmic Portfolio Management -- Financial analytics and decision-making strategies: future prospects from Bibliometrix based on R package -- MONETARY UTILITY FUNCTIONS AND RISK FUNCTIONALS -- Cryptocurrency Portfolios Using Heuristics -- Geographic Dispersion and IPO Underpricing -- The Rise of Fintech & Healthcare SPACs.-KOOPMAN OPERATORS AND EXTENDED DYNAMIC MODE DECOMPOSITION FOR ECONOMIC GROWTH MODELS IN TERMS OF FRACTIONAL DERIVATIVES -- Efficiency, taxation & solvency issues for SMEs: The case of Greece, Italy and Spain.
Keywords: Operations research; Financial engineering; Business -- Data processing; Financial risk management; Financial services industry; Management science; Operations Research and Decision Theory; Financial Engineering; Business Analytics; Risk Management; Financial Services; Operations Research, Management Science